2013
DOI: 10.1017/thg.2013.30
|View full text |Cite
|
Sign up to set email alerts
|

GWAS of DNA Methylation Variation Within Imprinting Control Regions Suggests Parent-of-Origin Association

Abstract: Imprinting control regions (ICRs) play a fundamental role in establishing and maintaining the non-random monoallelic expression of certain genes, via common regulatory elements such as non-coding RNAs and differentially methylated regions (DMRs) of DNA. We recently surveyed DNA methylation levels within four ICRs (H19-ICR, IGF2-DMR, KvDMR, and NESPAS-ICR) in whole-blood genomic DNA from 128 monozygotic (MZ) and 128 dizygotic (DZ) human twin pairs. Our analyses revealed high individual variation and intradomain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 57 publications
1
3
0
Order By: Relevance
“…In this study we detected a single nucleotide polymorphism rs10732516 G/A in the sixth-binding sequence of CTCF (CTCF6), which associated with the DNA methylation level of H19 ICR in placenta. Our finding was consistent with earlier studies, where whole blood samples were used (Coolen et al , 2011; Renteria et al , 2013) and encouraged us to explore the effects of alcohol exposure in a genotype-specific manner. Altered DNA methylation level at the CTCF6 showed an association with changes in IGF2 and H19 expression in a previous human study (Takai et al , 2001).…”
Section: Introductionsupporting
confidence: 91%
“…In this study we detected a single nucleotide polymorphism rs10732516 G/A in the sixth-binding sequence of CTCF (CTCF6), which associated with the DNA methylation level of H19 ICR in placenta. Our finding was consistent with earlier studies, where whole blood samples were used (Coolen et al , 2011; Renteria et al , 2013) and encouraged us to explore the effects of alcohol exposure in a genotype-specific manner. Altered DNA methylation level at the CTCF6 showed an association with changes in IGF2 and H19 expression in a previous human study (Takai et al , 2001).…”
Section: Introductionsupporting
confidence: 91%
“…It has been reported that allele‐specific methylation was strongly correlated with the genotypes at the sites (Zhang et al., 2009). Additionally, some studies have shown that epigenetic states interact with genetic sequences and suggested that SNPs within or outside some genes or regions are associated with the methylation states of these genes or regions (Murrell et al., 2004; Renteria et al., 2013). In these three genes, some DMSs are also SNPs and are close to GWAS SNPs.…”
Section: Discussionmentioning
confidence: 99%
“…Variants located within the nearest upstream or the nearest downstream genes of the following candidate genes, PLEKHH2 , LRPPRC , and SRBD2 , all located in the 2p21 locus, have also been reported as associated with various phenotypes according to the GWAS catalog database. Variants in THADA have been associated with age-related hearing impairment[ 44 ], Crohn's disease[ 45 ], DNA methylation variation[ 46 ], hair morphology[ 47 ], inflammatory bowel disease[ 48 ], mitochondrial DNA levels[ 49 ], orofacial clefts[ 50 , 51 ], platelet counts[ 52 ], polycystic ovary syndrome[ 53 , 54 ], prostate cancer[ 55 ], response to amphetamines[ 56 ], and type 2 diabetes[ 57 ]. Variants in ABCG8 have been associated with LDL cholesterol[ 58 63 ], total cholesterol[ 58 60 ], campesterol levels[ 64 ], and gallstones[ 65 ].…”
Section: Discussionmentioning
confidence: 99%